Quakerism: A Quest for Peace in the Road from Elephant Pass - Pokharel, Badri Prasad; Adhikari, Paras (Tribhuvan University Journal, 2018)
The 20th century ended very cruelly in different parts of the world with huge mass of massacres, blood shedding and terrorism which subsequently deteriorate human mind and people who were destined to live in terror, skepticism, and ultimately lack of belief not only in others but in self too. The intensive integration of sustainable peace has been preoccupied, but pragmatically such words remain in rhetoric. Quakerism with the inception of Quakers, a group of friends aligned with positive thinking for the conflict hit society, has embarked the contemporary war ridden society for human betterments, equality, progress and ultimately belief along with the inclination of happy and prosperous meme. Nihal de Silva, a Sri Lankan novelist best known for writing about the civil war that panicked the land for more than three decades has been remembered for bringing the trauma and anticipation of pacification in his works. His best and ever known novel The Road from Elephant Pass is analyzed and interpreted as a commencement of human betterment and sustainable peace in the long war ridden peninsula.